2020
DOI: 10.1523/jneurosci.2604-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Learning of Odor–Value Association in the Olfactory Striatum

Abstract: Rodents can successfully learn multiple novel stimulus-response associations after only a few repetitions when the contingencies predict reward. The circuits modified during such reinforcement learning to support decision-making are not known, but the olfactory tubercle (OT) and posterior piriform cortex (pPC) are candidates for decoding reward category from olfactory sensory input and relaying this information to cognitive and motor areas. Through single-cell recordings in behaving male and female C57BL/6 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 63 publications
10
50
1
Order By: Relevance
“…Such modifications were selective to the odor paired with phasic DA; hence, leaving the responses to other non-paired odors unchanged. Compatible with the concept that VS encodes the value of stimuli 13 , 24 , 39 – 41 , the decoding of stimulus representations increased after pairing with phasic DA. This increased distinctness of stimulus representation was also reflected in the perceived salience of the stimulus paired with phasic DA.…”
Section: Discussionmentioning
confidence: 96%
“…Such modifications were selective to the odor paired with phasic DA; hence, leaving the responses to other non-paired odors unchanged. Compatible with the concept that VS encodes the value of stimuli 13 , 24 , 39 – 41 , the decoding of stimulus representations increased after pairing with phasic DA. This increased distinctness of stimulus representation was also reflected in the perceived salience of the stimulus paired with phasic DA.…”
Section: Discussionmentioning
confidence: 96%
“…7 h). Olfactory tubercle could be the site for this odor–reward association 5 , 34 , but it could be other regions, such as layer 3 of piriform cortex, as well. To test performance of this circuit, we implemented a go/no go task in which one odor is associated with a reward ( R = 1.0), while another odor is associated with no reward ( R = 0.0), regardless of concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Learning, however, is particularly difficult, especially in natural environments where odors are rarely presented in isolation, most odors are presented a small number of times, and odor identities are rarely supervised. Nevertheless, animals can learn to associate an odor with a reward in a few trials 3 5 . Our goal here is to elucidate the local plasticity mechanisms that orchestrate this rapid learning.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that Tu neurons are recruited by stimuli that predict rewards upon conditioning (Gadziola et al, 2020, Millman and Murthy, 2020, Murata et al, 2015, Oettl et al, 2020, Zhang et al, 2017). In these studies, the duration of the conditioned stimulus partially overlaps with US.…”
Section: Discussionmentioning
confidence: 99%